Association Between Device-Measured Moderate-to-Vigorous Physical Activity and Academic Performance in Adolescents - Bueno, Maria Raquel de Oliveira; Zambrin, Lidyane Ferreira; Panchoni, Camila; Werneck, Andre Oliveira [UNESP]; Fernandes, Romulo Araujo [UNESP]; Serassuelo, Helio; Romanzini, Marcelo; Ronque, Enio Ricardo Vaz (Sage Publications Inc, 2020)
Background Although many studies found a positive association between physical activity (PA) and academic performance (AP), most did not consider important variables of school setting and students' self-concept. Aims To analyze the association between moderate-to-vigorous PA (MVPA) and AP in adolescents, considering potential confounding variables of school setting and self-concept in adolescents. Method The final sample was composed of 394 students (186 boys) with a mean age of 11.3 (SD= 0.8) years. The school grades were used as an indicator of AP. Measurements of body mass and stature were collected, and the body mass index was calculated and converted intoz-score values. Maternal education, socioeconomic status, self-concept, and variables of the school setting were self-reported. MVPA and sedentary behavior (SB) were measured through accelerometry (GT3X and GT3X+; ActiGraph, Pensacola, Florida). Multiple linear regression was used for the association analyses, adoptingp< .05. Results MVPA was inversely associated with global AP and mathematics only for girls: beta = -.105 (95% CI [-0.205, -0.006];p= .038); beta = -.136 (95% CI [-0.261, -0.011];p= .033). After adjusting for the school setting and self-concept, these significant associations disappear. Discussion MVPA was inversely associated with global AP and mathematics only for girls regardless of age,z-score body mass index, maternal education, socioeconomic status, and SB. However, after adjusting for school setting and self-concept, theses association disappear in mathematics and global AP, respectively. Conclusion The device-measured MVPA was not associated with AP after controlling for important variables (school setting and self-concept).
Keywords: motor activity; self-concept; school environment; school performance and youth